Efektivitas Ekstrak Binahong (Andredera cordifolia steenis) Terhadap Salmonella typhi secara in Vitro - Adriyan Suhada; Musparlin Halid; Wulan Ratia Ratulangi; Wulandari Dewi Susilawati; Uswatun Hasanah; Rizal Pratam Adi Putra; Pauzan; Hardani M.Si (Jurnal Penelitian dan Kajian Ilmiah Kesehatan Politeknik Medica Farma Husada Mataram, 2022)
Binahong (Anredera cordifolia steenis) is one of the plants that has the potential to be developed as a raw material for antibiotic drugs. Typhoid fever is a systemic infection caused by Salmonella typhi (S. typhi). Salmonella paratyphi A, B, and C can also cause an infection called paratyphoid fever. Typhoid and paratyphoid fever are included in enteric fever. In endemic areas, about 90% of enteric fever is typhoid fever. This study is a true experimental in the Biology lab of Politeknik Medica Farma Husada Mataram using the well method with 5 treatments, the treatment was repeated 6x with various concentrations of 100%, 80%, 60%, 40%, and 20%, and cipropolacin antibiotics were used as positive controls and ethyl acetate as a negative control, the material used is thick extract of binahong leaves, after the thick extract of binahong leaves is produced, then the antibacterial inhibition test is carried out against the growth of salmonella thypi bacteria in vitro, the parameter observed is the diameter of the antibacterial inhibition zone of salmonella thypi, ANOVA test data analysis. The results showed that binahong leaves have the ability to inhibit the growth of salmonella thypi bacteria with the inhibition zone formed. The average inhibition zone of binahong leaf extract (Anredera Cardifolia Steenis) is 20% concentration of 18mm, 40% concentration of 12 mm, 60% concentration of 15mm, 80% concentration of 19 mm, and 100% concentration of 24mm.